Interplay of interferon-gamma and macrophage polarization during Talaromyces marneffei infection. (September 2019) - Lu, Sha; Li, Dongmei; Xi, Liyan; Calderone, Richard
Abstract: Talaromyces marneffei is an increasingly destructive dimorphic fungal pathogen in clinical settings that can cause lethal Talaromycosis. The activation of macrophages is known to be important for host defenses against T. marneffei, and these macrophages are known to be activated in two ways (polarization), known as M1 and M2. We investigated the plasticity of these polarizations, in order to understand if cross-conversion of macrophages may be possible even after they have been programmed. We conducted in vitro experiments using a murine macrophage cell line to investigate the ability of T. marneffei to activate these polarizations. The pre-polarized (M0) macrophage subsets were challenged with LPS as a control, and the sets of M1 markers (iNOS and CD86) and M2 markers (Arg-1 and CD206) were assessed for a possible cross-conversion among M1, M2 and M0 (unstimulated) populations. We found that either conidia or yeast forms of T. marneffei initiate the repression of Arg-1 in M2 cells with no change in the M1 subtype marker molecule iNOS. However, an additional IFN-γ stimulus caused the three macrophage groups to fully exhibit an LPS-induced M2 suppression and a shift to M1 from M0 and M2. We conclude that the conversion of macrophages is required for maintenance of sufficient iNOS production against this organism in the host. The cytokine environment is the key factor that manipulates the plasticity changes among macrophage subtypes. Furthermore, IFN-γ is a crucial host defense factor against pathogenic T. marneffei that has significant therapeutic potential to promote an M1 polarization phenotype. Highlights: T . marneffei changes macrophage polarization in vitro . Polarization correlates with intracellular survival. New approach to intervention.